Multi-residue analysis of pharmaceutical compounds in wastewaters by dual solid-phase microextraction coupled to liquid chromatography electrospray ionization ion trap mass spectrometry - Unceta, N.; Sampedro, M.C.; Bakar, N.K.A.; Gómez-Caballero, A.; Goicolea, M.A.; Barrio, R.J. (2010)
The aim of this article is to present a new procedure based on dual solid-phase microextraction (dSPME) for the simultaneous extraction of 16 pharmaceutical compounds with acidic and basic characteristics in urban wastewaters. Water samples are divided into two aliquots of 2mL each extracted by two CW-TPR fibers at different pH values (pH 3 and 11) and with a NaCl concentration of 300gL-1 at 75Â°C for 30min. The analytes in both fibers are desorbed one after the other in the desorption chamber in static mode with mobile phase for 10min. The extracts are injected into an LC system coupled to an ion trap mass spectrometer, leading to the accurate quantification of 16 pharmaceutical compounds in wastewaters, in MS2 mode. All the target compounds found in wastewaters provide good signals corresponding to the protonated precursor ion M+H+. The parameters influencing adsorption and desorption of the analytes on fiber were optimized. The assessment of the analytical method was performed by studying the linearity (LOQ to 10ngmL-1) and the intra- and interday accuracy (89.2-109.7%) and precision (RSD <13.6%). The quantification limits obtained ranged between 0.005 and 0.05Î¼gL-1. The application of the method to real samples proves its effectiveness in identifying and detecting naproxen, valsartan, bezafibrate, torasemide, diclofenac, carbamazepine, citalopram, lorazepan, fluoxetine, imipramine and amitriptyline in influent and effluent wastewater treatment plant samples.